Moderating Effect of Trust on Determinants of Customer Satisfaction Factors - Muhammadinah, Muhammadinah; Palengka, Muhammad Fajri; Bayumi, Muhammad Rahman; Maulana, Chandra Zaky (Widya Cipta: Jurnal Sekretari dan Manajemen, 2025)
In connection with customer satisfaction of mobile banking users, there are several problems, including being vulnerable to “smishing” fraud, one of which involves rogue mobile applications. This study aims to determine the role of trust in moderating the effect of security level, and service features on customer satisfaction of mobile banking users of Bank Sumsel Babel Syariah UIN Raden Fatah Palembang Branch Office. This type of research is quantitative using statistical techniques to test the hypothesis. The data used is primary data with data collection techniques using questionnaires distributed directly to 100 respondents as samples with accidental sampling techniques while secondary data uses literature studies. The data analysis technique in this study uses SmartPLS with outer model testing including convergent validity, average variance extracted (AVE) and composite reliability and inner model testing including R square and hypothesis testing. The results showed that based on testing convergent validity, average variance extracted (AVE) and composite reliability, it is known that all variables including their indicators are declared valid and reliable, then the R-square value is 0.579 which means that customer satisfaction can be explained by 57.9% by the variables of security level, service features and trust, while the remaining 42.1% is explained by other variables outside the study.  Then the results of hypothesis testing show that the variables of security level, service features and trust directly have a positive and significant effect on customer satisfaction. Then the trust variable is unable to moderate the effect of the level of security and service features on customer satisfaction.